Pembuatan Aplikasi Sistem Portal Skripsi di Program Studi Teknik Informatika Universitas Kristen Petra Berbasis Website - Putera, Mahardhika Permana; Liliana, Liliana; Wibowo, Adi (Jurnal Infra, 2015)
At the moment, the Informatics Engineering Program needs a system that can manage an online registration, which can help in controlling the lecturers schedules and also a better way for theses title search. One problem that this department has, is in the system that controls the lecturers teaching quota that is currently having an issue. The issue is the fact that a lecturer could teach way more than the quota and vice versa. The process of scheduling and checking of the lecturers schedules for the theses proposal and theses defense is also a problem that raises in this department. However, the quota setting in this application will certainly could give an answer for both the lecturers and the students, since it will help making an equal division of the students quantity for each lecturer. Moreover, the application also offers a better way for theses title search in the sense that it makes the students easier to trace the previous theses titles that already existed and avoid any overlapping titles in the future. This theses title search feature uses SOLR technology to do a searching process that is counted based on the basic words from every searched word. The whole process in making this application is basically using yii framework and the database is using postgresql. Based on the testing result, this application succeeding to run smoothly. For additional thing in the future, this application can be added with a feature to check the theses titles that can no longer be used (already been used) and some title suggestions that are available (never been used yet).